Land use variation impacts on trace elements in the tissues and health risks of a commercial fish - N.D. Takarina; O.M. Chuan; T.G. Pin; I. Femnisya; A. Fathinah; A.N.B. Ramadhan; R. Hermawan; A. Adiwibowo (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Tropical coastal ecosystems globally have been affected by land use changes. This condition has caused a discharge of pollutants into the water, affecting marine organisms, including fish. Due to their habitat preferences, fish are prone to elevate heavy metals in their tissue. Considering fish is consumable, heavy metal levels in fish can lead to health risks. One of the common edible fish in Southeast Asia is Pennahia argentata. Although widely consumed, there is limited information on how land use influences heavy metal levels in various tissues of this species and its health risk. Fish is one of the main food sources in this region, indicating this information’s importance. This study aims to elaborate on and differentiate the heavy metal levels in tissues and land use types, including settlement and mangrove areas on the West Java coast of Indonesia.METHODS: Locations of this study are the Jakarta coast representing anthropogenic influences in the form of settlements and the Subang coast as a site of mangrove covers. This study combined remote sensing and Geographic Information System analysis with heavy metal analysis using inductively coupled plasma and studied heavy metals, including cadmium, copper, and zinc, in fish tissues such as the gill, digestive tract, and muscle. Differences and correlation of heavy metal data in each tissue and location were statistically analyzed using Pearson correlation values (r), Analysis of Variance, and x2-test. The estimated Daily Intake was used to determine the health risk consumption of this species.FINDINGS: All levels of heavy metals are below the World Health Organization’s permissible limits. Zinc is consistently high in all tissues and locations, while cadmium is the lowest. The result shows that the digestive tract consistently has the highest heavy metal levels compared to other tissues in both locations. Heavy metal in muscle has the lowest level. Copper and zinc in the muscles of fish living on the settlement coasts were 62.69% and 37.18% higher (P <0.05) than fish inhabiting mangrove coasts.CONCLUSION: Trace elements in the commercial fish P. argentata were significantly affected by differences in land use. Variations in land use have elevated heavy metal levels in fish tissues. Given the high levels of heavy metals, the digestive tract can be chosen as a specific fish tissue to be used as a bioindicator to monitor cadmium, copper, and zinc, particularly on the West Java coast in Indonesia. Because the Estimated Daily Intake for zinc in Jakarta is high, consuming fish should be done with caution.